EP1014 Signal transduction pathway activity in normal Fallopian tube epithelium and high-grade serous carcinoma. (1st November 2019) - van der Ploeg, P; Bucks, K; Bekkers, RLM; de Hullu, J; van de Stolpe, A; van der Wurff, A; Vos, MC; Piek, JMJ
Abstract : Introduction/Background: High-grade serous carcinoma (HGSC) is the most lethal gynecological malignancy due to late detection and high recurrence rates. New treatment options focus on targeted therapy based on signal transduction pathways (STPs). Tumour growth is induced by aberrant STP activation leading to disturbed cell proliferation and differentiation. However, knowledge about STP activity in healthy tissue is needed to discriminate STP activity in HGSC. As the Fallopian tube epithelium (FTE) is considered the tissue of origin of most HGSC, the aim of our study was to determine STP activity in normal FTE during the menstrual cycle compared to HGSC. Methodology: We included 10 lasermicrodissected FTE samples and 17 HGSC * . This study used Philips OncoSignal PCR, a diagnostic approach based on a computational model which infers quantitative STP activity from mRNA levels of pathway-specific target genes. Results: Preliminary data suggest that the follicular phase is characterized by high phosphoinositide 3-kinase (PI3K) pathway activity and the luteal phase by high androgen receptor (AR) pathway activity. Remarkably, no significant differences in estrogen receptor (ER) pathway activity were seen in the FTE during the menstrual cycle. In addition, ER activity was low in HGSC compared to normal FTE. High PI3K activity in HGSC was comparable with activity in the follicular phase. As proliferation is a hallmark of the follicular phase, it is suggested that up-regulation of the PI3K pathway in HGSC could be promoting proliferation and therefore be an interesting target for new therapeutic options. Conclusion: During the menstrual cycle, PI3K and AR pathway activity are activated in a strictly controlled manner. High PI3K activity in HGSC could indicate aberrant activation and may therefore be an attractive target. Future investigations should focus on post-menopausal FTE in order to further discriminate STP activity in HGSC. * Sample size will be expanded as the study is still ongoing. Disclosure: Nothing to disclose.